2021
DOI: 10.3390/nu13041361
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing in Chronic Migraine during the COVID-19 Outbreak: Results from a Multicenter Observational Study

Abstract: Background: The restrictions taken to control the rapid spread of COVID-19 resulted in a sudden, unprecedented change in people’s lifestyle, leading to negative consequences on general health. This study aimed to estimate the impact of such changes on migraine severity during 2020 March–May lockdown. Methods: Patients affected by migraine with or without aura, diagnosed by expert physicians, completed a detailed interview comprehensive of: assessment of migraine characteristics; measure of physical activity (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…This parameter is important, as recently demonstrated during the pandemic when both physical activity levels and sleep quality dropped in migraine patients [ 23 ]. The link between oxidative stress, physical activity, and sleep quality could somehow reside in the CGRP system [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This parameter is important, as recently demonstrated during the pandemic when both physical activity levels and sleep quality dropped in migraine patients [ 23 ]. The link between oxidative stress, physical activity, and sleep quality could somehow reside in the CGRP system [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we lack information of physical activity or dietary habits of the study subjects during the pandemic. These lifestyle elements may have an impact on patients during the pandemic [ 17 ]. Our goal is to present findings that can be representative of the real-world impact of COVID-19 on patients with migraine, given the rather large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication reported that the restrictions taken to control the rapid spread of COVID-19 resulted in a sudden, unprecedented change in the lifestyle of individuals, leading to negative consequences on general health ( 36 ). We recognized this problem in the decline of patients reporting regular physician care ( 37 ).…”
Section: Discussionmentioning
confidence: 99%